If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 16 + 7x + 4y Solving 0 = 16 + 7x + 4y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 0 + -7x = 16 + 7x + -7x + 4y Remove the zero: -7x = 16 + 7x + -7x + 4y Combine like terms: 7x + -7x = 0 -7x = 16 + 0 + 4y -7x = 16 + 4y Divide each side by '-7'. x = -2.285714286 + -0.5714285714y Simplifying x = -2.285714286 + -0.5714285714y
| 2-x/3=-5/2 | | -11/15+(-7/8)-(-1/6)= | | f(X)=3.14 | | 0=6-x+2y | | x+5.7=-6.8 | | 56x^2= | | 5-3z=z-16 | | 4x+x+5=2x-1 | | 11x-73=6x+77 | | 10x-5-7x=29 | | -30-3x=6y | | 75=6w | | 2x+-2=16 | | y+1=3(-7-2) | | 3b^2+40=-19b | | 5z-3z=z-16 | | -8-3y=-3x | | -x^2+4=3x-1x^2 | | 6(u-2)+2(u-53)=2 | | 0+1=3(x-2) | | -4y+16=-2x | | .2a=48 | | 6(a-7)+6=3(a-6) | | -2.2(n-.5)=-1.1(n-1.5) | | 4x^2+5=2x-1 | | 4*3-6*8+(-25)= | | 5x-5=2x+34 | | 3x=5y+5 | | 4+6x=18-(2-2x) | | 3b^2-40=-196 | | X+1+7=4 | | -5x+(-4-9)=6 |